A Comparative Study of Family Literacy Practices in Middle-Upper and Lower Socio-Economic Households in Cirebon, Indonesia - Aisyiyah, Muhsiyana Nurul; Yanuar, Ivo Dinasta (Equalita: Jurnal Studi Gender dan Anak, 2025)
Family is the smallest scope but has a huge impact on a person's literacy development. This research aims to potray the literacy practices of families who come from two different SES categories, middle-upper SES and lower SES. This research used a qualitative descriptive research design. Data was collected by conducting semistructured interviews. The research results show that there are different patterns between literacy practices in families with -middle-upper SES and lower SES. Families from middle-upper SES provide a variety of reading books that can attract children's interest in reading, while families with lower SES have limitations in providing books. The literacy activities in the two categories are also quite different. Parents in the middle-upper SES category tend to prioritize interaction, meaning making, values, and reading culture through storytelling and shared reading habits. Meanwhile, parents from lower SES tend to prioritize formal literacy such as introducing letters, teaching spelling, and numbers. Furthermore, in families with middle-upper SES background, both fathers and mothers are actively involved in home literacy activities. Meanwhile, Meanwhile, in families with lower SES backgrounds, gaps in parental involvement in family literacy practices were found. Mothers take a greater role than fathers in providing children's literacy experiences.